2022
DOI: 10.3389/fcimb.2022.961297
|View full text |Cite
|
Sign up to set email alerts
|

Tropheryma whipplei detection by metagenomic next-generation sequencing in bronchoalveolar lavage fluid: A cross-sectional study

Abstract: Tropheryma whipplei is the bacterium associated with Whipple’s disease (WD), a chronic systemic infectious disease primarily involving the gastrointestinal tract. T. whipplei can also be detected in different body site of healthy individuals, including saliva and feces. Traditionally, Tropheryma whipplei has a higher prevalence in bronchoalveolar lavage fluid (BALF) of immunocompromised individuals. Few studies have explored the significance of the detection of T. whipplei in BALF. Herein, we retrospectively r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
(36 reference statements)
1
12
0
Order By: Relevance
“…Seventy BALs (70/1725, 4.0%) from 70 patients were positive for T. whipplei . Only nine patients (12.9%) were immunocompromised [ 17 ]. For non-immunocompromised patients, the detection of T. whipplei needs to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Seventy BALs (70/1725, 4.0%) from 70 patients were positive for T. whipplei . Only nine patients (12.9%) were immunocompromised [ 17 ]. For non-immunocompromised patients, the detection of T. whipplei needs to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical symptoms of WD improve significantly within a few days to weeks after treatment with antibiotics, but WD requires a certain period of maintenance therapy to prevent recurrence ( 22 ). Nevertheless, WD has a lifelong potential for relapse, and Lin et al ( 6 ) suggested that the disease requires lifelong monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…The imaging manifestations of WD lung involvement are also diverse, with the most common chest imaging manifestations being nodules, interstitial changes and patchy infiltrates, of which nodules are the most commonly observed, with cavitation-like changes, pleural thickening and pleural effusion being less common ( 6 ). WD is mainly a chronic infection with multi-organ involvement, with occasional acute onset ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…to identify T. whipplei nurturing bodies, the disease is difficult to diagnose and is mainly confirmed using tissue biopsy and pathogenetic genetic testing[ 15 ]. Upon suspicion, despite gastrointestinal symptoms, small intestinal mucosal specimens should be obtained via microscopy for periodic acid Schiff staining, polymerase chain reaction (PCR), and mNGS testing[ 16 ]. If the results of small intestinal tissue examination are not diagnostic, the above tests should be performed by sampling the corresponding lesion sites (synovial membrane, lymph nodes, alveolar lavage fluid, cerebrospinal fluid, blood, etc. )…”
Section: Discussionmentioning
confidence: 99%